1995
DOI: 10.1002/eji.1830250121
|View full text |Cite
|
Sign up to set email alerts
|

Human eosinophils express a receptor for secretory component. Role in secretory IgA‐dependent activation

Abstract: The existence of a functional receptor for secretory component (SC) on the eosinophil membrane might explain the preferential degranulation induced by secretory IgA (sIgA) when compared to serum IgA. Indeed, flow cytometry analysis revealed that purified human SC could bind to a subpopulation (4-59%) of blood eosinophils purified from 19 patients with eosinophilia. Binding of radiolabeled human SC could be competitively inhibited using unlabeled SC or secretory IgA but not with serum IgA or IgG. Immunoprecipit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0
2

Year Published

1996
1996
2011
2011

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(63 citation statements)
references
References 36 publications
2
59
0
2
Order By: Relevance
“…Neutrophils do not have a specific receptor for SC (4), and SC did not interfere with IL-8 binding to specific, CXCR1 and/or CXCR2, receptors on neutrophils. In parallel, SC did not inhibit signaling via the IL-8 receptor.…”
Section: Discussionmentioning
confidence: 91%
“…Neutrophils do not have a specific receptor for SC (4), and SC did not interfere with IL-8 binding to specific, CXCR1 and/or CXCR2, receptors on neutrophils. In parallel, SC did not inhibit signaling via the IL-8 receptor.…”
Section: Discussionmentioning
confidence: 91%
“…2A) (17). Eosinophil activation by immobilized secretory component is correlated with the presence of a putative 15-kDa receptor for secretory component on eosinophils that is absent in neutrophils (43). The possibility that immobilized lactoferrin may cross-react with the putative receptor for secretory component on eosinophils (43) cannot yet be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to FcaR, SIgA has been shown to bind to an unidentified IgA receptor on human monocytes and that binding is blocked by galactose [83]. Moreover, a 15 kDa receptor for secretory component (SC) and thus also for SIgA has been identified on eosinophils but not on neutrophils [84]. Using different CD89 transfectant cell models, several studies have reported that pIgA binds more efficiently to FcaR than mIgA [85].…”
Section: Immunoglobulin-a Transportmentioning
confidence: 99%